PENGARUH MEDIA PEMBELAJARAN DIGITAL STORYTELLING TERHADAP MINAT BACA SISWA KELAS II SDN SUMUR WELUT III/440 SURABAYA - Safitri, Dita Ivana; Sumiharsono, Rudy; Danang Prastyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of digital storytelling learning media on the reading interest of class II students of SDN Sumur Welut III/440 Surabaya. This study was motivated by the lack of students' reading interest which is less than optimal. One of them is the teacher's accuracy in choosing learning media. The research method used is the quantitative causality research method. The population in this study was 60 students with the sample used being class II-A totaling 30 students. Data collection used questionnaires, interviews, and documentation. Data analysis used was validity test, reliability test, normality test, homogeneity test, and Paired Sample t-test. The results of the study showed the results of the validity test r table for df 28 and sig 0.05 in the r table of 0.361, it was stated that all questions in both variables X and Y were valid. The results of the reliability test of variable X show that the results of variable (X) show that the Cronbach's Alpha value> 0.9 and the results of variable (Y) show that Cronbach's Alpha> 0.9 stated that all questions from these two variables are stated to be reliable and very high. The results of the normality test show 200> 0.05. The results of the homogeneity test obtained a significance value based on the mean showing 0.086> 0.05. The results of the paired sample t-test show df = 29, then the table price of 1.699 from the results obtained t count> t table, namely 2.512> 1.699 or Sig value <0.05, namely 0.012 <0.05, which means that the data is stated to be significant. Thus it can be concluded that there is an influence of digital storytelling learning media on the reading interest of class II students of SDN Sumur Welut III/440 Surabaya.